INFLUENCE OF TRAINING WITH WEIGHT IN REDUCTION OF CORPORAL FAT AT ACADEMY OF UNIEVANGÉLICA. (Fiep Bulletin - online, 2015)
The force training is one of the basics properties of the motricity, by the side of the resistance, determining the physical profit(SPRING et al. 1995). The Working Out is a physical activity that has grown in the last years, being that the main objective of the majority of the people is the reduction of the corporal fat.  This made us to raise a question:  the force training influences in the reduction of corporal fat, when the same he is not allied to a aerobics session. The general objective of this study was to verify the influence of the training of force in reduction of the corporal fat, specific, to raise the index of corporal mass of academics of the UniEvangélica who working out as physical activity, with the objective of loss of weight.  Methodology, the study was realized in the academy of the UniEVANGÉLICA, with people with age understood between 15 and 50 years that practised training with weight with the objective to lose weight, the sample was composed for 32 people. The evaluations had occurred at the beginning and after of 12 weeks of training.  The evaluations anthropometrical had been made in the LAFE - UniEVANGÉLICA, and was composed for the measures of the weight, height and cutaneous folds, the percentage of Corporal Fat was esteem from the equations proposals for Jackson & Pollock.  The training was carried through in three weekly sessions with approach duration of 60 minutes, per 12 weeks.  The training consisted of a heating in the mat or bicycle per 10 minutes, after this heating, was mounted a program with weight, using exercises for superior, inferior members and trunk. RESULT There was prevalence in the age group of 17 to 26 years as it was waited, in function of the universitarian public who frequents the academy.  The initial adiposity of the sample for IMC follows the national gauge, 30% of overweight and 11% of obesity, 59% eutrophics.  These indices represent a reality of Brazil.  What more called us the attention was the corporal composition, initially was 29,3 ± 7,5 and to the end 25,3 ± 6,2. CONCLUSION - The force training revealed it self efficient in the reduction of corporal fat for practitioners of training with weights in the academy of the UniEVANGÉLICA;  The average of IMC of the practitioners with the objective of loss of weight is 26,05 ± 3,10;  The amount of people who had frequented the academy with the objective of loss of weight was of 195 people whose equivalent 42% of the total of practitioners.
Keywords: Working out; corporal composition; obesity.